THE RELATIONSHIP BETWEEN ENERGY AND NUTRIENT INTAKE WITH TRIGLYCERIDES/HIGH-DENSITY LIPOPROTEIN (TG/HDL) RATIO IN ADULT WOMEN - Arlen Defitri Nazar; Nur Indrawaty Lipoeto; Umi Fahmida; Rauza Sukma Rita (Jurnal Endurance, 2025)
The ratio of triglycerides to high-density lipoprotein (TG/HDL) is an important indicator in assessing the risk of cardiovascular disease. The intake of nutrients such as fats, carbohydrates, proteins, and PUFAs influences triglyceride and HDL levels in the blood. This study aims to see the relationship between energy intake and nutrients and the TG/HDL ratio in adult women. This cross-sectional study involved 158 adult women aged 25-44 years who were randomly selected, exclusion criteria were pregnant, taking drugs to lower blood cholesterol, and smoking. Energy intake data was collected using the interview method with SQ-FFQ by trained nutritionists and lipid profile data was obtained from blood tests using the spectrophotometer method with results in mg/dl. Blood sampling was carried out in the morning after the respondent fasted for about 10 hours, carried out by experts in the field of medical laboratories. Results of the lipid profile measurement were continued by calculating the TG/HDL ratio and statistical analysis with Spearman correlation. The results showed that 14% (22 people) had a high Triglycerides/HDL ratio value. The average Triglyceride level was 90.84 + 41.83 mg/dl, this value was still within the normal limit, while the average TG level in the group that had a high TG/HDL ratio was obtained with an average TG level of 163.27 + 50.99 mg/dl. Average HDL cholesterol levels were 52.93 + 12.86 mg/dl, and lower HDL levels were obtained in the group with a high TG/HDL ratio. The average energy intake was 124.7%, protein intake was 151.17%, carbohydrate intake was 103.63%, and fat intake was 158.82%. There was no significant correlation between energy intake, protein, carbohydrates, fat, fiber, and PUFA with TG/HDL ratio (p>0.05), but there was a tendency to negatively correlate between intake and TG/HDL ratio. Keywords : TG/HDL ratio; energy intake; protein; Carbohydrates; fat; PUFA